Theoretical and methodological foundations of social concepts of organ donation (The Journal of Psychology and Sociology, 2020)
The article deals with the social concepts of organ donation in the theoretical and methodological aspect, as well as analyzes the contradictions in the context of public relations, in connection with the presumption of consent and the presumption of disagreement. The purpose of the article is to consider interpersonal relations between the donor and recipient in socio-economic and economic-anthropolog- ical aspects. Despite the fact that in the era of scientific and technological revolution, medicine in the field of organ donation and transplantation is achieving significant success, the disparity between supply and demand for donor organs remains one of the most pressing problems in the world. Every year, the number of people who need donor organs on waiting lists around the world does not fall to low values.The article considers the relationship between the donor and recipient within the concepts of “circle of Kula”, “potlatch” in accordance with the concept of “gift exchange” by Marcel moss and the concept of “reciprocity” by Marshall Salins. The problem of genetic donation is analyzed based on the concept of generalized reciprocity by Marshall Salins.The theoretical and methodological aspects of the influence of positive and negative aspects of the presumption of consent and disagreement on society are analyzed. In addition, foreign experience, leg- islative acts, religious and ethical principles related to organ donation were considered.The results obtained in the course of theoretical research contribute to the resolution of contradic- tions in the public consciousness regarding organ donation, the formation of socio-economic, moral, and ethical conclusions regarding organ donation. The research materials and conclusions can be used in academic activities and in social medicine.Key words: organic exchange, Kula circle, gift exchange, reciprocity, presumption of agreement, presumption of disagreement, altruism.